1999
DOI: 10.1128/aem.65.2.374-380.1999
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of nifH Gene Pool Complexity in Soil and Litter at a Douglas Fir Forest Site in the Oregon Cascade Mountain Range

Abstract: Nitrogen-fixing microbial populations in a Douglas fir forest on the western slope of the Oregon Cascade Mountain Range were analyzed. The complexity of the nifH gene pool (nifH is the marker gene which encodes nitrogenase reductase) was assessed by performing nested PCR with bulk DNA extracted from plant litter and soil. The restriction fragment length polymorphisms (RFLPs) of PCR products obtained from litter were reproducibly different than the RFLPs of PCR products obtained from the underlying soil. The ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
85
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(93 citation statements)
references
References 28 publications
4
85
1
3
Order By: Relevance
“…Cluster A dominated in both root and soil fractions (56% of all sequences, Table 1). Because of this dominance, the diversity of nifH gene pools was low as compared to other studies (Ueda et al, 1995;Widmer et al, 1999). No sequence in cluster A was related to so far characterized NifH sequences from cultivated organisms.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…Cluster A dominated in both root and soil fractions (56% of all sequences, Table 1). Because of this dominance, the diversity of nifH gene pools was low as compared to other studies (Ueda et al, 1995;Widmer et al, 1999). No sequence in cluster A was related to so far characterized NifH sequences from cultivated organisms.…”
Section: Introductionmentioning
confidence: 69%
“…(Steenhoudt and Vanderleyden, 2000) were often described as being associated with grass roots. However, we did not detect any sequence related to these bacteria, even if the nifH genes from these organisms should have been amplified with the primers used (Widmer et al, 1999).…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…These bacteria may not be cultured by the methods used or may require metabolic interactions with other species normally present in planta but absent in pure culture. Recent PCR-based studies have revealed the presence of many unidentified and uncultured diazotrophs in such diverse habitats as rice roots [28] and forest litter [29]. In the case of the kallar grass/Azoarcus symbiosis, it has not been possible to re-isolate the bacterium even when the bacterium has been applied to sterile plants [40].…”
Section: Discussionmentioning
confidence: 99%